Comparative analysis of modulation strategies of bidirectional isolated AC-DC Matrix Converter. Issue 1 (1st June 2022) - Liu, Jinglin
Abstract: Bidirectional isolated AC-DC matrix converter is a new topology which has potential advantages in many aspects. But the topology of bidirectional isolated AC-DC matrix converter is complex, the front and rear circuits are coupled and interact with each other, it is difficult to decouple it directly, and it is difficult to modulate. So it is necessary to study its modulation strategy. In this paper, several existing modulation strategies are analysed and compared from three aspects: switching process, current stress and transmission power, and a relatively optimal modulation strategy is obtained. The superiority and correctness of the modulation strategy are verified by simulation.